Persistence in the Mint Stock Markets: Evidence from a Fractional Integration Model - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana; Oluwadare O. Ojo; Modupe I. Omotosho (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
This paper investigates persistence in the MINT (Mexico, Indonesia, Nigeria, Turkey) stock markets applying fractional integration methods to daily data from 1 January 2022 to 31 October 2025. Different model specifications are estimated for prices, log prices and log returns under the assumption of white noise and autocorrelated errors respectively. Mean reversion is found in most cases for prices with autocorrelated errors, which implies that shocks have only temporary effects in this case. Turkey displays the lowest degrees of integration, while Nigeria has the highest for both prices and log-prices. Structural breaks are found in the case of stock prices in all countries, with market inefficiencies appearing to be present in the most recent period characterized by geopolitical uncertainty resulting from the Russia-Ukraine conflict.
Keywords: C22; G12; 330; persistence; fractional integration; MINT; stock markets